Bahasa Inggris - Luthfansyah; Dwi Agus Sudjimat; Yayi Febdia Pradani (Universitas Negeri Padang, 2026)
This research is motivated by the low learning outcomes of students in the Technical Drawing subject at Vocational Schools due to the dominance of conventional methods that are less able to visualize objects comprehensively. The purpose of this study is to analyze the effect of using digital flipbook learning media on the learning outcomes of class X students of Welding Engineering Expertise Concentration at SMK Negeri 10 Malang. The research method used is quantitative with a One Group Pretest-Posttest design on 70 students selected through a total sampling technique. The research instrument is a validated multiple-choice objective test, and the data are analyzed using the Paired Sample T-Test and N-Gain tests. The results of the study showed a significant increase in the average value from 79.91 to 90.89 with a significance value of 0.000 (p < 0.05). The effectiveness of media use is in the